KISAH INSPIRATIF DALAM KEMASAN DAKWAH MEDIA: STUDI KASUS PROGRAM SELALU ADA HIKMAH TVONE - Wildani, Dani (Ulul Albab: Journal Da`wah and Social Religiosity, 2025)
The spread of da'wah through the mass media has a strategic role in distributing moral and religious messages to the community at large. One of the approaches that is considered effective is the use of inspirational stories that contain life values and messages of wisdom that are able to evoke the emotions of the audience. This research aims to examine how the packaging of inspirational stories is applied in the television da'wah program Always Ada Hikmah on TVOne The research approach uses a qualitative method with a case study type, through analysis of the content of the show and interviews with the production. The results of the study show that the program has succeeded in presenting a narrative that is full of Islamic messages with an easily acceptable delivery style, so it is expected to have a positive impact on public perception of da'wah on television media.